Rapid method for differentiating strains of Branhamella catarrhalis. - Peiris, V. (1992)
The ability of Branhamella catarrhalis to cause nosocomial infections is a matter of some controversy. The API ZYM research kit for detecting 89 enzymes was used on 49 isolates of B catarrhalis to select enzymes of potential use in differentiating clinical isolates. Twenty nine enzymes were produced by all isolates (13 strongly positive) and many of these were esterases; 16 enzymes were not detected in any isolate (40 if a more stringent criterion was used). Twenty enzymes were selected to form a prototype biotyping panel which allowed 17 different patterns of reactivity to be recognised. Of the 49, 34 isolates were confined to the three commonest patterns. Only one isolate was untypable using this panel due to lack of reactivity. A kit with these 20 substrates may be sufficiently discriminatory to be useful in the rapid study of outbreaks of infection caused by B catarrhalis.